KERANGKA PIKIRAN KEMAS ULANG INFORMASI : SUATU KAJIAN BERPKIRAN DESAIN - Arwendria (UIN Imam Bonjol Padang, 2022)
Design thinking has been widely used by researchers in various fields to design products that are suitable for their target groups. This study used literature research to reveal the theoretical use of this method for information repackaging. The results showed that the design thinking method could be applied to information repackaging, both with model of the IDEO and 3I Brown, The Six Phases of HPI, or The Seven Stages. The iterative nature of the design-minded could increase the validity, reliability and practicality of the information repackaging products